Development of E-Modules Based on PBL Model to Improve Critical Thinking Skills on SPLTV Material - Ahmad Rizal; Puguh Wahyu Prasetyo (Universitas Ahmad Dahlan, 2025)
Entering the era of the Industrial Revolution 5.0, critical thinking skills are an important aspect of education, especially in learning mathematics. However, students' critical thinking skills in Indonesia are still low, including in the material of System of Linear Equations of Three Variables (SPLTV). One solution is the use of the (PBL) model supported by an interactive e-module. This study aims to develop and analyze the effectiveness of PBL-based e-modules in improving students' critical thinking skills. The research method used is the ADDIE model with the subject of class X students at SMA Negeri 1 Tahunan. The validation results showed that the e-module was very valid, with an average score of 41.5 for media and 42.1 for material. The practicality test obtained a score of 78.2 (category